Teaching Arabs, writing Self - Amina Inloes (International Institute of Islamic Thought, 2015)
Teaching Arabs, Writing Self traces Evelyn Shakir’s evolution from a budding student of canon English literature who was desperately trying to “become white” to her epiphany that stories from her own working-class immigrant neighborhood might be of equal worth. There, she found her unique niche by becoming an author and scholar of Arab-American literature who helped gain recognition for this literature as a genre, and who helped readers see Arab Americans as people rather than stereotypes. Shakir divides her memoirs into three sections. In the first, she reflects on her childhood during an era that frowned upon diversity. Like many immigrant children, she turns up her nose at the “wrong” foods: “Bread with pockets. Hummus and tabouli. ‘Don’t put that stuff in my lunch box,’ I said” (p. 8). She even goes so far as to join a Methodist church whose quiet, orderly simplicity seems more “American” than her family’s ritualistic but expressive Orthodox church. Acculturated to the “Protestant disdain for Eastern churches and, by extension, for the East itself,” only later does she develop “[a]n inkling that there might be treasures I had turned my back on. That I might not always have to be ashamed” (p. 13). In this section, we see the historical value of Shakir’s work not only as a personal memoir, but also as an account of twentieth-century Americana. Born in 1938, she offers a rare narrative voice of that era – that of a Lebanese- American and a woman; a handful of personal photos literally offer a rare glimpse into the society of Arab-American women. Many of her childhood memories center on Boston’s nearby Revere Beach, which boasted “slot machines spitting out weight, fortune, photos of Rita Hayworth,” “Dodgems (‘no head-on collisions’ but we did),” and “clams in a Fryolator … corn popping frantic in a display case … frozen custard (banana my favorite) spiralling thick-tongued into waffle cones, then dipped headfirst in jimmies” (p. 32). Her true claim to Americanhood is that her uncle ran the beach’s “glitzy” Cyclone roller coaster, which “gave me bragging rights among my friends and helped situate me closer to the American norm that was always just beyond my reach” (p. 29). The Cyclone was so important to the beach’s identity that its closure in 1969 signaled the demise of the beach itself. “It’s those cars that tell the story,” she recollects. “As soon as masses of people could afford them, Revere lost its reason for being” (p. 43) ...